Assessing TikTok for Language Learning and Pedagogy: Challenges of Public Hoax Information - Israr, Mohammad; Aeni, Nur; Abduh, Amirullah (Journal of Language Learning and Assessment, 2025)
Purpose This research aims to find out the impact on the spread of hoaxes on social media, especially TikTok. How the TikTok recommendation algorithm affects the spread of hoax news, how TikTok user behavior, including interaction, sharing and content consumption, is related to the spread and control of hoax news and to find out what impact hoax news spreading via TikTok has on public trust, public opinion and social decisions.   Methodology This research uses descriptive qualitative research methods as the main research methodology. This qualitative descriptive research uses an online survey method in the form of a questionnaire distributed via platforms such as Google Forms. Apart from the survey, face-to-face in-depth interviews were also conducted at a predetermined place. The sampling technique used in this research was purposive sampling.   Result/Findings The finding of this research indicated that a majority of respondent’s report using Tik Tok for 1 to 2 hours, with 26.5% using it for more than 2 hours. The majority of social media users use Tik Tok for entertainment, including dance and music videos (2.9%). However, Tik Tok has also developed into a platform that provides all kinds of information, including hoaxes that can spread widely. In the respondents' opinion, false information is something that is very detrimental if it continues to circulate on TikTok. One respondent stated that TikTok hoaxes have the potential to cause hatred or fear and have the potential to exacerbate political, social or religious conflict.   Implication This research contributed to address this critical gap in the literature by examining the influence of TikTok social media in curbing and filtering hoax news. By conducting a comprehensive analysis of Tik Tok's content ecosystem, user behaviors, and its approach to content moderation, this study aims to shed light on TikTok's role in the broader discourse surrounding miss information and the promotion of factual information in the digital era.